Pengaruh Edukasi Gizi Terhadap Pengetahuan, Pola Makan Dan Kadar Glukosa Darah Pasien Diabetes Melitus Tipe 2 RSU Kota Mataram Dengan Provinsi NTB - Susilawati, Wulandari Dewi; Hasanah, Uswatun (Research of Service Administration Health and Sains Healthys, 2023)
The phenomenon of diabetes mellitus from year to year an increasing number. One major factor is the lack of knowledge in conducting therapy in patients with diabetes mellitus diit so may lead to increased blood sugar  levels.  The  aim  of this  study  was  to determine  the  effect  of nutrition  education  to increase  the knowledge, dietary compliance and uncontrolled blood sugar levels Type 2 Diabetes Mellitus Outpatient in Kota Mataram Dg Provinsi NTB Public Hospital Jeneponto. The design of this research was experimental studies  with pre experimental designs  One Group Pretest And Postest Design. Sampling was conducted using purposive sampling technique with a sample of 30 people. Data was collected by the secondary data and primary data. The dietary pattern data was collected by 24 hours recall questionnaire, blood glucose level of patients were measured  by blood  glucose  meter.  While  the knowledge  of patients  were  collected  by interview  using questionnaire.given  before and after the education. Height and weight of patients were measured by scale and microtoice. The secondary data are the description of hospital and laboratory result data obtained from the  hospital.  Data  analysis  was  performed  by  Mc  Nemar  test.The  results  showed,   after  education, knowledge of patients categorized sufficiently increased (p = 0.031), from 33.3% to 53.3%, as well as the diet of patients (p = 0.003), from 23.3% to 60 , 0% categorized fairly, as well as the patient's blood sugar levels were controlled (p = 0.000), from 3.3% to 46.7%. It is recommended to patients to better manage diet to control blood sugar levels with the help of physical activity and obedient in taking the drug.